2019
DOI: 10.2147/cmar.s202394
|View full text |Cite
|
Sign up to set email alerts
|

<p>Whole exome sequencing of multiple meningiomas with varying histopathological presentation in one patient revealed distinctive somatic mutation burden and independent clonal origins</p>

Abstract: Background: Although meningiomas are common intracranial tumors, multiple meningiomas (MMs) are rare entities in patients without neurofibromatosis type 2. Previous studies suggest most sporadic MMs are of monoclone in origin. Objective: To elucidate the clonal relationship between two sporadic meningiomas from the same patient by using the next-generation sequencing (NGS) platform. Methods: Two MMs, located frontally and parietally on the right side, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…The genomics of familial MMs is also well understood with known inherited driver germline mutations in NF2, SUFU , or SWI/SNF complex ( SMARCE1, SMARCB1 ) genes [ 8 10 ]. While the molecular basis for the formation and development of sporadic MMs has been suggested to be through either mono- or multi-clonal (i.e., independent from one another) formation [ 11 , 12 ], the genomic studies to test these hypotheses have been limited [ 13 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genomics of familial MMs is also well understood with known inherited driver germline mutations in NF2, SUFU , or SWI/SNF complex ( SMARCE1, SMARCB1 ) genes [ 8 10 ]. While the molecular basis for the formation and development of sporadic MMs has been suggested to be through either mono- or multi-clonal (i.e., independent from one another) formation [ 11 , 12 ], the genomic studies to test these hypotheses have been limited [ 13 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although meningioma is the most common primary tumor of the central nervous system, the mechanism of progression from benign to atypical or anaplastic grade remains elusive [5]. It has been suggested that the atypical tumor may have progressed from the benign tumor.…”
Section: Discussionmentioning
confidence: 99%
“…It can occur sporadically or as part of a familial syndrome of either neurofibromatosis type II or familial multiple meningiomas [4]. The incidence of sporadic multiple meningiomas without history of neurofibromatosis type II was low [5]. Multiple meningiomas usually show a uniform histology, but the synchronous meningiomas of different grades have been reported and may be formed independently due to separate genetic mutation and aberrant pathway expressions [6].…”
Section: Introductionmentioning
confidence: 99%
“…DNA was isolated from tumor tissues, the patient's peripheral lymphocytes, and his parents' peripheral lymphocytes as described before ( 11 ). The quality of isolated DNA was assessed by using 1% agarose gel electrophoresis and Qubit ® DNA Assay Kit in Qubit ® 2.0 Fluorometer (Life Technologies, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The WES protocol was similar to the one we used previously ( 11 ). Briefly, DNA libraries were prepared using the Agilent SureSelect Human All Exon kit (Agilent Technologies, Santa Clara, CA, USA) following the manufacturer's recommendations, and index codes were applied to each sample.…”
Section: Methodsmentioning
confidence: 99%